Pengaruh Financial Attitude dan Fintech Literacy pada Financial Inclusion (Studi Kasus Pada Mahasiswa UPN Veteran Yogyakarta) - Koraag, Satrio Tegar Gunung; Pratita, Mutya Paramita (Jurnal Paradigma, 2024)
Abstract   This research aims to investigate the impact of Financial Attitude and Fin-Tech Literacy on financial inclusion among UPN Veteran Yogyakarta students who use Go-Pay services. A total of 200 respondents were selected using a non-probability sampling method. Data analysis was carried out using Smart PLS statistical test tool. The research results show that both Financial Attitude and Fin-Tech Lietracy have a significant and positive influence on student financial inclusion. These findings highlight the positive role of financial attitudes and fintech literacy in encouraging student involvement in financial inclusion, particularly through the use of Go-Pay. This research provides valuable insights for the development of financial inclusion programs in academic environments, emphasizing the importance of understanding and improving financial attitudes an fin-tech literacy in supporting students’ active participation in digital financial services such as Go-Pay.